A REVIEW ON THE ICHTHYOFAUNAL DIVERSITY IN MANGROVE BASED ESTUARY OF KADALUNDI RIVER, KERALA, SOUTH INDIA - AKSHAD, M. ALI; ANSARI, V. SHAHEER (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
A review on the Ichthyofaunal diversity in Mangrove based estuary of Kadalundi River, Kerala, South India was during July, 2016, to June, 2017. It is located on the Western side of the Northern Kerala, in Kozhikode and Malappuram districts on the river mouth of Kadalundipuzha spreading in the estuary. Total 37 fish species were reported belonging to 29 families were reported from the 3 selected stations. The total population density of station-A, B and C was 2004, 1868 and 2090 respectively. The maximum number of species was reported in three stations in the month of October. The minimum species was reported in the month of January. The maximum number of species was reported in station-A (254) and minimum number of species was reported in station-A (87). The maximum number of species was reported in station-B (243) and minimum number of species was reported in station-B (70). The maximum number of species was reported in station-C (253) and minimum number of species was reported in station-C (103).